Nutrition Status as Determinant of Incidence of Measles in Jember Regency - Lailatul Rahmawati; Isa Ma'rufi; Farida Wahyuningtyias (Health Notions, 2018)
Measles disease is a communicable disease and leading causes of infant mortality. Jember regency is one of the contributors of high measles cases in 2010 there were 123 cases. In 2011 there were 128 cases. In 2012 there were 64 cases. In 2013 there were 45 cases, in 2014 there were 112 cases, in 2015 there were 109 cases, there were 266 cases in 2016. In 2017 to July there were 342 cases the number of measles incidents is very high compared to 2016. One of the risk factors for the disease is the host factor, host factor including age, immunization, nutritional status. The purpose of this study is to analyze the factors that influence the incidence of measles in Jember Regency. The method used was analytical with case control approach, the sample of research were 50 cases and 50 controls. Data analysis used is logistic regression test (α = 0.05). The result of analysis showed that there was an influence of nutritional status on measles incidence in Jember Regency, children with less nutrition had 2.113 times greater risk for measles compared with children with more nutrition and there are no influence of age and immunization on measles in Jember District. Keywords: Measles, Age, Immunization, Nutritional status